Optimizing Hydraulic Retention Times in Denitrifying Woodchip Bioreactors Treating Recirculating Aquaculture System Wastewater. Issue 3 (1st May 2016) - Lepine, Christine; Christianson, Laura; Sharrer, Kata; Summerfelt, Steven
Abstract : The performance of wood‐based denitrifying bioreactors to treat high‐nitrate wastewaters from aquaculture systems has not previously been demonstrated. Four pilot‐scale woodchip bioreactors (approximately 1:10 scale) were constructed and operated for 268 d to determine the optimal range of design hydraulic retention times (HRTs) for nitrate removal. The bioreactors were operated under HRTs ranging from 6.6 to 55 h with influent nitrate concentrations generally between 20 and 80 mg NO3 − –N L −1 . These combinations resulted in N removal rates >39 g N m −3 d −1, which is greater than previously reported. These high removal rates were due in large part to the relatively high chemical oxygen demand and warm temperature (∼19°C) of the wastewater. An optimized design HRT may not be the same based on metrics of N removal rate versus N removal efficiency; longer HRTs demonstrated higher removal efficiencies, and shorter HRTs had higher removal rates. When nitrate influent concentrations were approximately 75 mg NO3 –N L −1 ( n = 6 sample events), the shortest HRT (12 h) had the lowest removal efficiency (45%) but a significantly greater removal rate than the two longest HRTs (42 and 55 h), which were N limited. Sulfate reduction was also observed under highly reduced conditions and was exacerbated under prolonged N‐limited environments. Balancing the removal rate and removal efficiency for this water chemistry with a design HRT of approximately 24 h would result in a 65% removal efficiency and removal rates of at least 18 g N m −3 d −1 . Core Ideas: Woodchip bioreactor design parameters for aquaculture wastewater were developed. This application resulted in the highest N removal rates reported (39 g N m −3 d −1 ). Retention times differ for optimized removal efficiency versus removal rate. Sulfate reduction intensified under prolonged N‐limited environments.